EDITORIAL. - Fahlander, Fredrik; Högberg, Anders (Current Swedish Archaeology / Svenska Arkeologiska Samfundet, 2015)
An introduction is presented in which the editor discusses various reports within the issue on topics including the contribution of English language on Anglo-Saxon dominance, theory building in archaeology, and Object-Oriented philosophies.